A new analysis model for borehole stability in gas drilling. Issue 4 (October 2021) - Zhuo, X; Liu, X; Shi, X; Liang, L; Ding, Y
Abstract: Gas drilling is one of the main underbalanced drilling techniques, which has a significant effect on the ROP (rate of penetration) improvement in hard formation. However, because the circulating medium in drilling process is gas instead of liquid, the fluid column pressure of gas drilling cannot provide enough support force for the rock around borehole as that of conventional overbalanced drilling. Due to the combination influence of engineering and geological factors, the borehole rock is prone to instability during gas drilling, which can lead to rock blocks falling from the well wall and the formation of irregular borehole shape. To avoid the occurrence of complex underground accidents caused by too many falling rock blocks, such as the borehole instability and pipe-sticking, it is necessary for gas drilling to take into consideration the true triaxial stress state of the rock in the deep formation and the possibility of the borehole breakout. Based on the permitted breakout angle of borehole and true triaxial strength theory of rock, an analysis model of borehole stability has been developed for the engineering of gas drilling. The theory of linear elasticity, involved in this analysis model, is used to analyse the stress state of rock around a cylindrical hole under lower wellbore pressure. The failure of the rock around borehole is determined by the Mogi-Coulomb criterion, which considers the intermediate principal stress effect on rock material. The results show that the model is as simple and practical as the traditional model, which takes no account the effect of the intermediate principal stress or the permitted borehole breakout, and it can provide an accurate analysis for the borehole stability of gas drilling. Therefore, the results of this study, combined with the related work such as the prediction of water formation, can guide the adaptability evaluation for the engineering design of gas drilling.